2011
DOI: 10.1016/j.ajpath.2011.04.020
|View full text |Cite
|
Sign up to set email alerts
|

The mTOR/AKT Inhibitor Temsirolimus Prevents Deep Infiltrating Endometriosis in Mice

Abstract: Deep infiltrating endometriosis (DIE) is a particular clinical and histological entity of endometriosis responsible for chronic pelvic pain and infertility. Here we characterize the proliferative phenotype of DIE cells, to explore the cellular and molecular mechanisms that could explain their aggressive potential. In addition, the inhibition of mTOR/AKT pathway was tested, as a potential treatment of DIE. Included were 22 patients with DIE and 12 control patients without endometriosis. Epithelial and stromal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 48 publications
3
88
0
1
Order By: Relevance
“…Previous in vitro studies using human umbilical vein endothelial cells and human pulmonary microvascular endothelial cells have demonstrated that endothelial cell viability and proliferation are blocked by temsirolimus or rapamycin at lower drug concentrations (0.1-100 nM) (4,8,47,58). In vivo studies have also shown that rapamycin treatment augments lung injury induced by BLM or lipopolysaccharide in mice with acute lung injury (17,28). Clinically, serum Krebs von den Lungen 6, which is a biomarker of interstitial lung disease and is associated with epithelial cell injury and capillary-alveolar permeability changes, is elevated in patients with everolimus-induced ILD (24,34).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Previous in vitro studies using human umbilical vein endothelial cells and human pulmonary microvascular endothelial cells have demonstrated that endothelial cell viability and proliferation are blocked by temsirolimus or rapamycin at lower drug concentrations (0.1-100 nM) (4,8,47,58). In vivo studies have also shown that rapamycin treatment augments lung injury induced by BLM or lipopolysaccharide in mice with acute lung injury (17,28). Clinically, serum Krebs von den Lungen 6, which is a biomarker of interstitial lung disease and is associated with epithelial cell injury and capillary-alveolar permeability changes, is elevated in patients with everolimus-induced ILD (24,34).…”
Section: Discussionmentioning
confidence: 81%
“…Temsirolimus (1 and 10 mg·kg Ϫ1 ·day Ϫ1 for the lowand high-dose groups, respectively) or vehicle was administered 3 days/wk for 2, 4 or 8 wk. The doses and dosing interval of temsirolimus were chosen based on previous studies (28,56) that evaluated tumor growth inhibition and hematological toxicities of temsirolimus at doses of 3-100 mg·kg Ϫ1 ·day Ϫ1 in mice and the following unpublished company data (Pfizer): a single intravenous dose of 1 mg/kg temsirolimus in mice resulted in areas under the plasma concentra-tion-time curves of temsirolims (1,460 ng·h Ϫ1 ·ml Ϫ1 ) and sirolimus (2,470 ng·h Ϫ1 ·ml Ϫ1 ), which were equivalent to those (1,349 and 3,793 ng·h Ϫ1 ·ml Ϫ1 , respectively) in patients repeatedly treated with the recommended dose (25 mg) of the drug. At the end of the dosing period, animals were anesthetized with pentobarbital (120 mg/kg ip) and euthanized by exsanguination, and samples were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have found that phospho-Akt and phospho-mTOR are elevated in postmenopausal endometriosis. mTOR/Akt inhibition by temsirolimus could decrease endometriotic cell proliferation both in vitro and in vivo [24]. Besides, it is reported that transient hypoxia in transplanted endometriosis-like lesions results in the upregulation of hypoxia-inducible factor-1α (HIF-1α) and then expression of vascular endothelial growth factor (VEGF), leading to endometriosis angiogenesis, a pathogenesis of endometriosis [25].…”
Section: Discussionmentioning
confidence: 99%
“…This mTOR is a protein kinase that controls protein synthesis related to cell growth and proliferation, and all mTOR inhibitors act by binding to mTOR with high specificity (46). Human endometriotic cells display a hyperproliferative phenotype that is associated with activation of the mTOR pathway.…”
Section: Immunomodulatorsmentioning
confidence: 99%